Effectiveness of WeChat Official Accounts in health communication: A comparative study of hospitals and centers for disease control and prevention on resident participation in Shenzhen - Fangfang Gong; Li Zeng; Yi Li; Jingang Shi; Ke Huang; Ying Zhou (Digital Health)
Background As China transitions from a disease-centered to a people-centered healthcare model, hospitals are increasingly involved in health education. This study compares the effectiveness of WeChat Official Accounts (WOAs) operated by hospitals and Centers for Disease Control and Prevention (CDCs) in engaging residents and identifies strategies to enhance the dissemination and impact of hospital WOAs in digital health communication. Methods This observational study utilized WcplusPro to collect health education-related articles posted between July 2023 and June 2024 from WOAs of district-level CDCs and hospitals in eight administrative districts of Shenzhen, China, excluding administrative affairs-related content. The effects of different posting organizations on article reading and sharing were compared using chi-square tests and multivariable logistic regression in R. Results A total of 2270 health-related articles were selected for analysis. CDC WOAs accounted for 59.34% ( n  = 1347) of the posts, while hospital WOAs accounted for 40.66% ( n  = 923). Articles posted by hospitals showed a significant positive association with high reading levels (OR = 14.69, 95% CI = 9.96–22.25). For sharing levels, articles posted by hospitals showed a significant positive association with high sharing levels (OR = 3.56, 95% CI = 2.71–4.72). Articles were more likely to achieve higher resident engagement ( p  < 0.05) if they were published by accounts with larger follower bases (OR = 59.01), featured interrogative titles (OR = 22.19), avoided threatening tones (OR = 4.98–15.44), or were highlighted as headlines (OR = 25.03). Conclusions Hospital WOAs demonstrate higher effectiveness in promoting resident participation in health education. Hospitals should link health services to daily life and use emotionally resonant narratives. They should expand followings, refine headlines, and position. Encouraging healthcare professionals in health education can boost participation.